Redescription of some bryozoan species originally described by J. Jullien from Iberian waters - Souto, Javier; Reverter-Gil, Oscar; Fernández-Pulpeiro, Eugenio (Zootaxa, 2011)
Six species originally described by Jules Jullien from Iberian waters are redescribed from the original material and stabilized by typification: Caberea ligata, Bicellaria evocata, Scrupocellaria marsupiata, Setosella folini, Euginoma vermiformis and Jubella enucleata. Caberea ligata is placed here in the genus Canda, not previously reported from European waters. Scrupocellaria marsupiata is differentiated from Menipea clausa, previously considered as a junior synonym; both species are placed in the genus Notoplites. A diagnosis is given for the family Jubellidae, the position of which is discussed.